Congenital Hypothyroidism – An Update (Bangladesh Journal of Child Health, 2018)
Hypothyroidism is a common disorder of the endocrine system in which the thyroid gland does not produce enough thyroid hormone. The most cases of congenital hypothyroidism (CH) is from thyroid dysgenesis. The worldwide incidence CH is 1:3000- 4000 live births and prevalence rate of CH in Bangladesh is 0.9%. The thyroid gland is the first endocrine structure in fetus. Triiodothyronine (T3) and thyroxine (T4) appear by 12 weeks of gestation. CH is classified into permanent and transient. Permanent CH requires life-long treatment. Common symptoms of CH are feeding difficulty, prolonged jaundice, lethargy, constipation and not growing well. Newborn with CH will have puffy face, wide posterior fontanelle, wide open sutures and later on umbilical hernia, coarse facies, macroglossia and cold or mottled skin are common signs. Measurement of T4 and TSH as newborn screening are appropriate approach with interpretation of T4 below 10th centile or TSH above 90th centile or absolute cut-offs such as T4 < 6.5 ug/dL and TSH > 20mu/L. The diagnosis of primary CH is confirmed by the finding of an elevated serum TSH level and a low free T4 or total T4. Early T4 replacement in children with CH is crucial for neurological outcome. A high starting dose of 10–15 ìg/kg/day is recommended by AAP and European Society for Paediatric Endocrinology (ESPE). The T4 levels normalize in first 3 days of initiation of treatment, while TSH levels take up to 1 month for normalization. Routine follow-up with biochemically adjustment of doses of Levothyroxine can completely normalize the children of CH.Bangladesh J Child Health 2017; VOL 41 (2) :110-116